EQUILIBRIATE CALCULATIONS FOR BUSINESS EXPANSION WITH ANALYZE USING MICROSOFT VISUAL BASIC 6.0 - Ani Hermawati; Irfan Irfan, Skom, MMSI (Jurnal Sistem Informasi, 2003)
In making a particular product, the management requires an analysis that helps inmaking decisions when to expand the company's business and knowing the amount ofproduct at breakeven so the company could expect a benefit. Then use any of theanalysis is breakeven analysis.